KONSEP MANUSIA IDEAL DALAM PEMIKIRAN HAMKA (The Concept of Ideal Man in HaMka Thoughts) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The title of the research is "The Concept of Ideal Man in Hamka Thought". In the circle of Indonesian Moslem thinkers one of his thoughts explains about the formation of ideal man. The aim of the research is to deepen and analyze Hamka's thought about ideal man. The characteristic of the research is based on library research, so, the data of Hamka's thoughts have been collected including the data which is relevant and related to the object of the study. The data was analyzed by using hermeneutic-philosophy method and descriptive, comparative, syntetic-analysis and critically-reflection approach. This research found that: 1. The system of Hamka's thought is categoriÂ¬cally more Sufism. 2. The concept ideal man of Hamka was influenced by Neo-Platonism, Moslem philosophers, Sufism, and al-Asy'ariyah theology. 3. The concept of ideal man of Hamka is accord and compatible with the concept of Indonesia man which have the caharacteristics of Pancasila perÂ¬sonality. That characteristics stress the balance of soul-body, individu-so-cial, and independent being-God creature. The concept of ideal man have to be developed in Indonesia for purpose of supporting the development of Indonesia man totally.